Farmers' Perception of EBN Farm Radio Programme in Tambol-Sadej of Huang District, Lampang Province, Thailand - Kamka, Sanun (1989)
The objectives of this study were : (1) to determine the farmers' perception of EBN farm radio programme, (2) to describe the radio listening behaviour of the farmers, (3) to determine the relationship between farmers' perception and some demographic, socio-economic, and communication factors. The study also tried to formulate guide line s for agricultural radio broadcasting. A total of 183 farmers from eight villages of Tambol-Sadej, Muang district, Lampang Province Thailand were selected by using a simple random sampling method. Data were gathered by personal interviews and analysed by using the Statistical Package for the Social Sciences (SPSS PC+).